DC microgrid with hybrid photovoltaic storage system: Control strategy optimization using improved Archimedes optimization algorithm - Han, Ye; Han, Ye-Xin; Lim, Ming K.; Tseng, Ming-Lang (Journal of energy storage, 2025)
This study contributes to select the system voltage fluctuation as the optimization objective and uses Improved Archimedes optimization algorithm (IAOA) to analyze the control parameters for DC microgrid. DC microgrids containing hybrid energy storage play an important role in energy utilization efficiency, system stability, operating costs, intelligent management and clean energy development. ESS significantly enhances the stability of the DC microgrid by regulating power balance, suppressing voltage fluctuations, and providing rapid power support. Hybrid photovoltaic storage system (HESS) is controlled by low-pass filter and double closed-loop control. The control strategy based on synchronized generator characteristic is adopted for the microgrid inverter. Yet, prior studies are neglecting to involve the control strategy optimization for the microgrid inverter. This study proposes an improved Archimedean optimization algorithm control method based on the Levy flight strategy to improve the DC microgrid system stability incorporating HESS. IAOA is used to find the optimal control parameters adapted to the overall system considering the interaction between microgrid inverter and HESS. This study substitutes the optimized control parameters into the model for simulation to verify the effectiveness of DC microgrid optimization. The control strategy based on IAOA optimization reduces the voltage fluctuation amplitude by 1.6 %–6.98 % when the simulated model is disturbed by analyzing with the traditional sag control. •This study is based on the photovoltaic DC microgrid with hybrid energy storage system.•Bus voltage-based distribution strategy is used for hybrid energy storage system.•The control strategy of the inverter considers the characteristics of the synchronous generator.•The effect of hybrid energy storage on the inverter control parameters is considered.•An improved Archimedes optimization algorithm is proposed for the optimization of control parameters.